2014
DOI: 10.1111/hir.12081
|View full text |Cite
|
Sign up to set email alerts
|

The role of health information kiosks in diverse settings: a systematic review

Abstract: The results suggest that health information kiosks are a feasible medium to disseminate health information among various users in clinical and community settings, with high acceptance and satisfaction by users. Theoretical driven interventions are needed to examine long term impacts of health information kiosks especially in rural and underserved populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Beyond printed materials, there has been a lack of innovative approaches to education in the waiting room that both robustly utilize available technologies and also attempt to reach underserved groups [9]. Thus, maximizing the appropriateness and efficacy of educational resources for underserved populations requires assessment of the context and thoughtful choice of format.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond printed materials, there has been a lack of innovative approaches to education in the waiting room that both robustly utilize available technologies and also attempt to reach underserved groups [9]. Thus, maximizing the appropriateness and efficacy of educational resources for underserved populations requires assessment of the context and thoughtful choice of format.…”
Section: Introductionmentioning
confidence: 99%
“…Less than half of those that did undertake quality assessment (11 of 26) actually defined what they meant by quality. Eight studies defined quality as an assessment of the methodological quality (Koufogiannakis and Wiebe, 2006;Zhang, Watson, & Banfield, 2007;Joshi & Trout, 2014;Golder & Loke, 2009Perrier et al, 2014;Gagnon et al, 2010;Divall, Camosso-Stefinovic, & Baker., 2013), and three studies (Perrier et al, 2014;Gagnon et al, 2010;Divall et al, 2013) specified quality as the risk of bias. Two studies defined quality assessment as assessing the quality of the study design, or level of evidence (Manning Fiegen, 2010;Ndabarora, Chipps, & Uys, 2014).…”
Section: Reporting Of Quality Assessment Methods In Lis Systematic Rementioning
confidence: 99%
“…The number of authors undertaking quality assessment in a systematic review ranged from 1 to 8. Three studies (Joshi & Trout, 2014;Manning Fiegen, 2010;Perrier et al, 2014) reported an assessment of the inter-rater agreement of quality assessment between reviewers. Nine studies reported using quality assessment as part of their inclusion and exclusion criteria.…”
Section: Reporting Of Quality Assessment Methods In Lis Systematic Rementioning
confidence: 99%
“…The main aim of these solutions is to improve the shopping experience and customer satisfaction by offering them additional services [17]. Another domain increasingly popular is health care, where kiosk-based systems' advantages are well-known [18]. In this field, researchers focus on developing self-service solutions either for health-related information distribution [19], education [20] or health condition monitoring [21].…”
Section: Related Workmentioning
confidence: 99%